THE EFFECT OF ADDITION BISPHENOL-A-POLYCARBONATE FROM CD-R WASTE AS A CATALYST FOR HYDROGEN PRODUCTION - Mas'ud, Sifa'ul; Sulaiman, Abdul Mudjib; Syahputra, Hogi; Purnami, Purnami (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
In producing hydrogen, various methods can be used, one of which is the electrolysis of water. Electrolysis is a method for breaking water molecules into oxygen and hydrogen by using an electric current. Electrolysis does not require complicated equipment and systems, so it can be said to be the easiest method of producing hydrogen. But of the various methods for producing hydrogen, the electrolysis method is not widely used because of its low efficiency. Because of this, many efforts have been made with the aim of increasing hydrogen production in the electrolysis of water. In this paper, we use Bisphenol-A-Polycarbonate (BPA) compounds obtained from unused CD-R layers. BPA has aromatic compounds that have been tested by FTIR. Aromatic compounds can generate their own magnetic field; this magnetic field is used to disrupt hydrogen bonds in water so that the electrolysis process can be more optimal. It is also known that, on the surface of BPA, it has a tendency to be positively charged by FESEM testing. The predominantly positive BPA surface works effectively to attract OH- ions. This causes a lot of H+ ions to move freely so that the solution becomes more acidic, which results in easier mobility of electric currents. With the addition of 3 grams of BPA, it can produce 46% more ppm of hydrogen than conventional.